Assessing Applicability of eDNA‐Based Sampling for Population Monitoring of Leatherback Turtles in the Northeast Indian Ocean - As‐singkily, Maslim; Nijland, Reindert; Bista, Iliana; Dutton, Peter H.; Becking, Leontine E. (Environmental DNA (Hoboken, N.J.), 2025)
ABSTRACT Current population genetics studies of sea turtles primarily rely on invasive tissue sampling or blood draws, which involve the capture and handling of the animals that require specific permits and resources. Moreover, this approach is limited by the sporadic visibility of turtles. In this study, we assessed the applicability of eDNA‐based sampling to obtain mitochondrial haplotype data for leatherback turtle (Dermochelys coriacea) populations at three beaches in Sumatra, Indonesia (Northeast Indian Ocean). We collected seawater samples at two time points: immediately after a female left the beach (night samples) and 12 h later (morning samples) to reflect the common practice of conducting beach monitoring surveys at dawn. Our findings revealed that the eDNA samples captured identical haplotypes to those obtained from tissue samples. The haplotypes persisted in the eDNA from seawater samples up to 12 h after the females left the beach. We identified five haplotypes that correspond to those previously recorded in the Pacific, Atlantic, and Indian Oceans, showing the broad phylogeographic links between the Sumatra population and other global populations. Our results provide further evidence that noninvasive eDNA techniques could supplement traditional tissue sampling for studying sea turtle population genetics. This applies particularly to understudied populations or remote rookeries where traditional methods are difficult to implement and opens the possibility of using eDNA for population structure studies that could complement traditional monitoring programs. We evaluated the feasibility of environmental DNA (eDNA) sampling to obtain mitochondrial haplotype data for leatherback turtles at three nesting sites in Sumatra, Indonesia. Our results demonstrate that eDNA‐based sampling can reliably capture haplotypes identical to those from tissue samples and that eDNA persists in seawater for up to 12 h post‐nesting, supporting its application for dawn‐based monitoring. These findings highlight eDNA as a non‐invasive tool for sea turtle population genetics, with potential applications in conservation and biomonitoring.